The role of communication in the implementation of the performance management system in the South African Public Services : a case study of the Department of Trade and Industry - Matlala, Mokgadi Martha (My University, 2017)
The performance of public sector institutions has been the subject that has attracted attention of policy makers. This is because the long-established role and institutional character of the State has been under scrutiny as the result of not being able to achieve the desired outcomes which were evidently visible in as far as the performance of public sector organisations were concerned. It is largely because of this reason that the quest for increasing the efficiency and effectiveness of public sector institutions became very critical. Most scholars mentioned have written extensively on the discourse, but have focused squarely on assessing the implementation of the PMS, neglecting the importance of 'communication' as the central pillar required for having achieved the desired implementation of such a system. As a result, very little is known about the role of communication in the process of implementing PMS in the South African public service. Thus, the implementation of PMS continues to face many serious challenges. The aim of the study was to examine the role of communication in the implementation of PMS in the South African public service, using DTI as a case study with the view of gaining insight into the contribution that communication can make in improving public service performance through effective implementation of PMS. The study utilised both the qualitative and quantitative research methods to investigate the role of communication in the process of implementing PMS in the South African public service. Questionnaires were distributed to employees from level 5-11 and semi-structured interviews were conducted with employees from level 12-13 in the DTI. The study concludes that communication plays a greater role in the implementation of PMS and that there is still lack of effective communication within the department. The implementation of the PMS in the department is inconsistent across the different Chief Directorates and that it is often difficult to measure employee performance in that regard. Communication within the department is from top to bottom, whereby senior managers (Directors) instruct the middle managers (Deputy Directors) from level 12-13, lower and middle management (Assistant Directors) on how to implement the PMS with less consultation from their subordinates.
Thesis (MPA.) --University of Limpopo, 2017.
Keywords: Performance management; Department of Trade and industries; Communication; Performance management